Review paperFood allergy Part IV – Hen’s egg - Rudzki, Edward (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
In the paper the following issues are discussed: 1) white and yolk hen’s egg antigens, 2) immediate and delayed reactions due to these eggs, 3) sensitivity to raw and boiled eggs, 4) hidden sources of allergens, 5) cross-reactions with eggs from other birds, 6) prevalence of sensitivity in children and adults, and 7) sensitivity of hen\'s eggs in patients with atopic dermatitis, urticaria, asthma, egg-bird syndrome, oral allergy syndrome and ulcerative colitis.